Updating the Species Inventory of Large- and Medium-Sized Mammals in China Based on 2009–2020 Field Observation Records - Shuyi Zhu; Jia Tian; Jianbing Yue; Fei Duan; Sheng Li (Animals)
Large- and medium-sized mammals (LMMs) are closely related to humans and perform critical functions in the ecosystem. China harbors one of the richest mammalian faunas in the world, whereas there is an urgent need among wildlife managers and researchers to update the inventory of China’s LMM species based on recent empirical information. In this study, we compiled the occurrence records of terrestrial LMMs in China during 2009–2020, mainly from camera-trapping surveys, through a comprehensive literature search and systematical data collection. With a total of 42,937 occurrence records (12,397 after removing duplicates) from 5461 sites, we recorded 134 LMM species belonging to 8 orders and 23 families. Compared to the national species list, seven species are missing from field observation records, including four of Carnivora, two of Primates, and one of Lagomorpha. Yunnan is the province with the highest richness of recorded LMMs (n = 69), and Xizang is the only province where all seven large apex predators have been recorded. This study systematically updates the species inventory of LMMs in China based on observation records and will provide an important baseline to support and guide future studies, monitoring, and conservation management of this important functional group in China.